2009
DOI: 10.1002/hed.21192
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cervical metastases with 11C‐tyrosine pet in patients with squamous cell carcinoma of the oral cavity or oropharynx: A comparison with 18F‐FDG PET

Abstract: Because of bilateral accumulation of (11)C-TYR in salivary glands, (11)C-TYR PET is not suitable to replace (18)F-FDG PET in staging SCC of oral cavity and oropharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The main problem with early 18 F‐FDG PET/CT evaluations in this context is the deficient specificity of the method due to tracer uptake in inflammatory cells. Use of amino‐acid tracers has been proposed to circumvent this problem but the intense uptake of these tracers in the salivary glands might be a new source of false‐positive findings 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with early 18 F‐FDG PET/CT evaluations in this context is the deficient specificity of the method due to tracer uptake in inflammatory cells. Use of amino‐acid tracers has been proposed to circumvent this problem but the intense uptake of these tracers in the salivary glands might be a new source of false‐positive findings 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…PET/MRI has a higher sensitivity in assessing soft tissue infiltration in comparison to MRI. 18 F-FAMT can be used to assess bone marrow involvement [13,4042]. …”
Section: Imaging Methods In Oral Cancermentioning
confidence: 99%
“…The incorporation of tyrosine explains this into secretory proteins synthesized in salivary glands. 239,377,378 However, a later study to detect cervical metastases revealed the unsuitability of [ 11 C]tyrosine due to the increased bilateral uptake in the salivary glands, which impaired the visualization of metastases located within this area. 378 Therefore, [ 11 C]tyrosine is probably unsuitable for imaging the liver, pancreas, or salivary glands due to high accumulation in these organs.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Studies performed in patients with prolactinomas, a benign pituitary gland tumor that produces an excessive amount of the hormone prolactin, assessed the effect of bromocriptine treatment, showing the potential use of this radiotracer for investigating the salivary glands. The incorporation of tyrosine explains this into secretory proteins synthesized in salivary glands. ,, However, a later study to detect cervical metastases revealed the unsuitability of [ 11 C]­tyrosine due to the increased bilateral uptake in the salivary glands, which impaired the visualization of metastases located within this area . Therefore, [ 11 C]­tyrosine is probably unsuitable for imaging the liver, pancreas, or salivary glands due to high accumulation in these organs.…”
Section: Amino Acidsmentioning
confidence: 99%